Picture Of Age Factors And Sexual Activity With The Incidence Of Benign Prostate Hyperplasia - Hamdana; Fatmawati (Comprehensive Health Care, 2017)
In Indonesia Prostate Hyperplasia Benigna Based on the autopsy rate of microscopic changes at the age of 30-40 years. When microscopic changes develop, anatomic pathologic changes occur in men aged 50 years, the incidence rate is around 50%. 80 years old around 80% and 90 years old 100%. Prevalence increases because of an increase in life expectancy. The results of a survey conducted on Benigna Prostate Hyperplasia patients at H. Andi Sulthan Daeng Radja Hospital in Bulukumba District, patients with Benigna Prostate Hyperplasia have an average age of> 50 years as many as 30 people. This study aims to determine the description of age and sexual activity with the incidence of hyperplasia prostate benign disease in H. Andi Sulthan Daeng Radja District Hospital. This study uses a descriptive approach with a population of 30 and is sampled. Sampling using the Total Sampling method. The results of research on the incidence of prostate hyperplasia benign disease mostly occur with age and partial sexual activity who experience benign prostatic hyperplasia more normal sexual activity 1-2 times/weeks and only a few are abnormal sex frequency. The conclusion of the study is the age category of the initial elderly as many as 7 people (23.3%), the final elderly as many as 8 people (26.7%). While the age of seniors as many as 15 people (50%) the category of normal sex frequency <3 times/week as many as 16 respondents (53.3%) and as many as 14 respondents (46.7%) who do sexual frequency> 3 times a week. The suggestion from this research is that it should pay attention to various aspects that can influence the occurrence of hyperplasia prostate benign in patients so that its incidence can be prevented and can provide good service, as well as the right action for sufferers of benign prostatic hyperplasia.